Gema Kriya di Tengah Jagad Budaya - Sugiharjanto, Asto Adi; Toekio, Soegeng (KEMADHA, 2011)
Indonesia as an archipelagic country as well as a maritime nation that is rich  in  customs  and  lush  islands  in  bantangan  equator .  The  country  also recognize  the  diversity  in  cultures  and  ethnic  groups  scattered.  Indigenous culture that was born of the tribes in many cases the common feature would also imaging,  including a wealth of material culture  is very diverse. When  the concept of blown art  complements  the  realm of  science and  technology, his position became increasingly taken into account. Many efforts and tips to find novelty in the  concept  and  engineering  of  this  material.  One  phenomenon  which  is currently  less preached,  is  the existence kekriaan as one kind of  Indonesian art In  the  atmosphere  created  by  dualism mainstream  of  the  developing nations, will require many wise minds to be able to form a renewal without any cultural conflict. Negative picture of the atmosphere that can only be a source of catastrophe for the existence of cultural assets that no longer have a place to exist. However , it does not mean that the old habits that rests on peradatan was then  terluluhkan.  Actually  there  are  superior  power  of  indigenous  culture (ethnicity) and has a strong desire to keep strong in the midst of a global culture. Excellence  that  has  been  proven  true  history  has  shown  its  reputation  and acknowledged able to appear in the middle of chess world. Some of them would not even be something that is familiar , such as: batik, wayang, gamelan, keris / tosanaji, weaving, plaiting, grabah, and other kria products  that use natural ingredients.Similarly, wide opportunities to enter the constellation of global culture, but it is very unfortunate that the impact of multi-cultural arena that makes the attitude of complacent. Theres homework to explore the local idioms become a source  of  knowledge  that  was  valid  and  the  accelerated  nature  of  arena global.Dari rich repertoire of such kekriaan  it  is possible  to  tampil. Beside that, the sources of art in the barn and spread culture, still only in conditions hardly budge.Exposure is inclined to open a portion of the map kekriaan which allows to be explored to further packed into bertara information science. Like a pearl that  has  not  been  honed,  the  sources  kekriaan  will  put  the  validity  of  the archipelago  when  art  idiom  be  appointed  as  part  of  the  taxonomy  of  art.